Fluorescent molecular rotors as versatile in situ sensors for protein quantitation - Kevin Daus; Sorachat Tharamak; Wanchai Pluempanupat; Peter A. Galie; Maria A. Theodoraki; Emmanuel A. Theodorakis; Mary L. Alpaugh (Scientific Reports, 2023)
Abstract Accurate protein quantitation is essential for many cellular mechanistic studies. Existing technology relies on extrinsic sample evaluation that requires significant volumes of sample as well as addition of assay-specific reagents and importantly, is a terminal analysis. This study exploits the unique chemical features of a fluorescent molecular rotor that fluctuates between twisted-to-untwisted states, with a subsequent intensity increase in fluorescence depending on environmental conditions (e.g., viscosity). Here we report the development of a rapid, sensitive in situ protein quantitation method using ARCAM-1, a representative fluorescent molecular rotor that can be employed in both non-terminal and terminal assays.